Temporal Governance and Public Inclusion: A Sociopolitical Study of Civil Service Delivery Innovation in Bali - Hapsari, Komang Heny Tri; Prabawati, Ni Putu Anik (Universitas Pattimura, 2025)
This study examines public service innovation through the